Undang-Undang Pornografi Dalam Tinjauan Politik Hukum Pidana - Khakim, Mufti (Faculty of Law, Universitas Ahmad Dahlan, 2016)
Advances in technology has a big contribution in the spread of pornography, even it has a considerable advantage for the business of pornography. On the other hand, emerging social restless and the government will also impact negatively on pornography especially with regards to the mentality of the young generation. Nowadays, pornography can be enjoyed by all people start from children to the elders by the help of technology it makes easier for people to access this site.The offenses of pornography set in Law Number 44 of 2008 was full of controversy even after have been set, it still reap the rejection of the society. The Government considers that it is time for pornography to regulate specifically so it will not cause restless in the community even though its been many laws offering pornography. Dangers of pornography take a big part in the mental damage of the young generation it becomes a specific reason why this case needs to be set firmly.InÂ the politics of criminal law view, it is necessary to study in-depth whether the govern-ments action to regulate pornography in a special law by imposing criminal sanctions are appropriate with the prospects of the people. Regulation of pornography needs to be completed perfectly or it will be better if the regulation be eliminated completely. Conclusions taking technique of this study is using deductive analysis.